The effect of antecedent rainfall on slope stability - Rahardjo, Harianto (2011)
A case study is presented in order to identify the effect of antecedent rainfall on slope stability for Singapore. A storm in February 1995 (during which 95 mm of rain fell in 2 1/2 h) caused more than twenty shallow landslides on the Nanyang Technological University Campus. Details of the location, size and morphology of the landslides are presented. The antecedent rainfall during the five days preceding the event was significant in causing these landslides since other rainfall events of similar magnitude (but with less antecedent rainfall) did not cause landslides. To further understand the effect of antecedent rainfall, numerical modelling of one of the slope failures is presented. The changes in pore-water pressure due to different rainfall patterns were simulated and these were used to calculate the changes in factor of safety of the slope. The results demonstrate that antecedent rainfall does play an important role in slope stability.